THE IMPLEMENTATION OF SCIENTIFIC APPROACH IN FINANCIAL ACCOUNTING LEARNING TO VOCATIONAL SCHOOL STUDENTS AND ITS EFFECTS TO STUDENTS’ HIGHER-ORDER THINKING SKILLS - L. Saptono (Jurnal Cakrawala Pendidikan, 2016)
Abstract: This research was aimed to investigate: 1) how is the implementation of scientific approach in financial accounting learning to vocational schools of business (SMK) students, in the field of business and management skills, financial skills program, package of accounting skills in Special Region of Yogyakarta; 2) the correlation of the implementation of scientific approach in financial accounting learning in the field of business and management skills, financial skills program,  package of accounting skills with the level of students’ higher-order thinking skills. This research was descriptive. The research was conducted from October 2014 to July 2015. The students of SMK in the field of business and management skills, financial skills program, and package of class XI accounting skills in Special Region of Yogyakarta that have received material bank reconciliation in the academic year 2014/2015 were the population of this research. The total of research samples were 1,388 students. Sampling technique used was purposive sampling. Data collection techniques in the study were questionnaires and tests. The data then were analyzed using descriptive statistic and Spearman correlation.  The findings of this research showed that: 1) the implementation of scientific approach in financial accounting learning to vocational school of business (SMK), the field of business and management skills, financial skills program, package of accounting skills in Special Region of Yogyakarta was very good (mean = 29.73 on a scale of 7-35); 2) there was positive correlation of the implementation of scientific approach in financial accounting learning in the field of business and management skills, financial skills program,  package of accounting skills with the level of higher-order thinking skills of students (Spearman's rho (rs) = 0.135; sig. (2-tailed) = 0.000 a = 0.05).Keywords: scientific approach, higher-order thinking, vocational school of business